STATCOM Model for Integration of Wind Turbine to Grid - Rajib Baran Roy; Md. Rokonuzzaman (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to reduce the green house gas emission and dependency on conventional energy sources, the utilization of renewable energy sources for electricity generation is increasing day by day. The performance of the wind turbine as well as the power quality is determined according to the guidelines and regulations of IEC-61400 (International Electro-technical Commission) standard. When wind turbine is connected to a grid system, the power quality measurements like active power, reactive power, frequency, voltage sag, voltage swell, ﬂicker and harmonics are needed to be considered. In this paper, a STATCOM (static compensator) model is proposed for improving the power quality in case of feeding electricity generated from the wind turbine into the grid.The proposed STATCOM control scheme for improving the wind power quality is designed and simulated by using Simpower toolbox of MATLAB Simulink. According to the simulated results, the bus voltage is improved after adding STATCOM in the simulated model which justifies the feasibility and practicability of the proposed FACTS (Flexible AC transmission system) device.